2014
DOI: 10.1002/mrc.4174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ions on water structure: a low‐field 1H T1 NMR relaxometry approach

Abstract: Aqueous salt solutions play an important role in nature because of their effects on environmental biogeochemical processes and on structural properties of biomolecules. Upon dissolution, salts split in ions that are solvated. Water in hydration shells is subjected to molecular motions that can be monitored by (1)H T1 NMR relaxometry. This technique allowed the evaluation of the nature of the interactions between water and ions via variable temperature experiments. Examination of relaxometry properties of aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…The interactions between water and the organic constituents of biochar can be obtained through the electron-donation from the π-clouds of the polyaromatic systems towards the electron-deficient hydrogens in water. This may lead to weak unconventional H-bonds between the asymmetrically shaped hydrated nitrate ions 58 and the porous biochar surfaces. Moreover, Conte et al 56 recently showed that water movement in a pyrogenic poplar biochar was slow at temperatures up to 50 °C due to strong surface bonding forces; these forces considerably weakened at 80 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between water and the organic constituents of biochar can be obtained through the electron-donation from the π-clouds of the polyaromatic systems towards the electron-deficient hydrogens in water. This may lead to weak unconventional H-bonds between the asymmetrically shaped hydrated nitrate ions 58 and the porous biochar surfaces. Moreover, Conte et al 56 recently showed that water movement in a pyrogenic poplar biochar was slow at temperatures up to 50 °C due to strong surface bonding forces; these forces considerably weakened at 80 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore r 1 was determined through a single point measurement of R 1 according to Eqn 1. The value of R 1W was calculated according to Eqn 2 for chaotropic salts and to Eqn 3 for kosmotropic salts . The values of β + were −0.019 (K + ), +0.057 (Na + ) and +0.24 (Ca 2+ ) and the value β − was −0.019 (Cl − ) .…”
Section: Resultsmentioning
confidence: 99%
“…The value of R 1W was calculated according to Eqn 2 for chaotropic salts and to Eqn 3 for kosmotropic salts . The values of β + were −0.019 (K + ), +0.057 (Na + ) and +0.24 (Ca 2+ ) and the value β − was −0.019 (Cl − ) . R 1 obs is the measured relaxation rate constant (=1/ T 1 ), R 1W is the relaxation rate constant of the solvent in the absence of the Gd 3+ chelate, and R 1 0 is the longitudinal relaxation rate constant of water in the absence of both Gd 3+ and salt. truer1=H2OGd3+(R1obs-R1W) trueR1W=R10{}1+saltβ++β- trueR1W=R10{}saltexpβ++β- …”
Section: Resultsmentioning
confidence: 99%
“…The capturing and release of cations and anions in biochar are most likely because of the following: Water bridging – i.e. water bridges between the hydration shells surrounding the dissolved ions and the hydrophilic systems, such as inorganic ashes and oxy‐genated organic functions, on biochar surfaces (Conte, ). Ionic bonding – i.e. direct ion bonding to positive, respectively, negative charged micro sites, functional surface groups or precipitated metal oxides or pyrolytic tars. Covalent bonding – i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Water bridgingi.e. water bridges between the hydration shells surrounding the dissolved ions and the hydrophilic systems, such as inorganic ashes and oxy-genated organic functions, on biochar surfaces (Conte, 2014).…”
Section: Multispecies Nutrient Binding Mechanisms and Time-dependent mentioning
confidence: 99%